Three Novel Loci for Infant Head Circumference Identified by a Joint Association Analysis - Yang, Xiao-Lin; Zhang, Shao-Yan; Zhang, Hong; Wei, Xin-Tong; Feng, Gui-Juan; Pei, Yu-Fang; Zhang, Lei (Frontiers in Genetics, 2019)
As an important trait at birth, infant head circumference (HC) is associated with a variety of intelligence- and mental-related conditions. Despite being dominated by genetics, the mechanism underlying the variation of HC is poorly understood. Aiming to uncover the genetic basis of HC, we performed a genome-wide joint association analysis by integrating the genome-wide association summary statistics of HC with that of its two related traits, birth length and birth weight, using a recently developed integrative method, multitrait analysis of genome-wide association (MTAG), and performed in silico replication in an independent sample of intracranial volume (N = 26,577). We then conducted a series of bioinformatic investigations on the identified loci. Combining the evidence from both the MTAG analysis and the in silico replication, we identified three novel loci at the genome-wide significance level (α = 5.0 × 10−8): 3q23 [lead single nucleotide polymorphism (SNP) rs9846396, pMTAG = 3.35 × 10−8, preplication = 0.01], 7p15.3 (rs12534093, pMTAG = 2.00 × 10−8, preplication = 0.004), and 9q33.3 (rs7048271 pMTAG = 9.23 × 10−10, preplication = 1.14 × 10−4). Each of the three lead SNPs was associated with at least one of eight brain-related traits including intelligence and educational attainment. Credible risk variants, defined as those SNPs located within 500 kb of the lead SNP and with p values within two orders of magnitude of the lead SNP, were enriched in DNase I hypersensitive site region in brain. Nine candidate genes were prioritized at the three novel loci using multiple sources of information. Gene set enrichment analysis identified one associated pathway GO:0048009, which participates in the development of nervous system. Our findings provide useful insights into the genetic basis of HC and the relationship between brain growth and mental health.